GAP ANALYSIS PROGRAM GIZI DAN KESEHATAN DI POSYANDU KABUPATEN BOGOR - Ellis Endang Nikmawati; Clara Meliyanti Kusharto; Ali Khomsan; Dadang sukandar; Arum Atmawikarta (Food and Nutrition Society of Indonesia, 2009)
Revitalization of Integrated Service Center Post (Posyandu) is successful when focused to its main function as community institution services. Determine gap analysis program based on tangibles, reliability, responsiveness, assurance, empathy dimension. Exploratory and experimental designs was applied in this study, which was conducted at Darmaga and Ciomas district, Bogor Regency from March to August 2008. The data included primary and secondary data. The respondent in the experiment was 240 mothers of children under five years and 80 cadres. Gap analysis was used to know the expected and the real nutrition and health program of respondent. Totally 96 balita’s mother, pregnancy and reproductive women and 16 cadres were involved in this study. The average of gap realization with standard tool -0,75; Tangibles dimension -0,35; Reliability -0,10; Responsiveness -0,37; Assurance -0,44, and Empathy -0,47, its mean that a tools accomplisment only 25% (less); tangible dimension 65% (enough); reliability 90% (good); responsiveness dimension 63% (enough); assurance dimension 56% (less) and emphaty 53% (less), respectively.